2008
DOI: 10.1590/s0004-282x2008000300019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the effects of cyclosporine in the brainstem of Wistar rats submitted to the ethidium bromide demyelinating model

Abstract: -The ethidium bromide-demyelinating model (EB) was used to study remyelination in the brainstem under the use of cyclosporine (CsA). Wistar rats were submitted to intracisternal injection of 0.1% EB or 0.9% saline solution, and others were taken as histologic controls (group I). Within those injected with EB, some have not received immunosuppressive treatment (II); some were treated by intraperitonial route with CsA (III.E -10 mg/kg/day). Rats from group III.C were injected with saline solution and treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 21 publications
(36 reference statements)
3
18
0
Order By: Relevance
“…A greater proportion of oligodendroglial cells on the edges of demyelinating lesions was seen in rats treated with cyclosporine (CsA) after the injection of ethidium bromide (EB) in the rat brainstem 1 . This gliotoxic agent is known to induce early astrocyte disappearance and oligodendroglial loss when injected in the central nervous system (CNS) leading to, respectively, blood-brain barrier disruption and primary demyelination.…”
mentioning
confidence: 99%
“…A greater proportion of oligodendroglial cells on the edges of demyelinating lesions was seen in rats treated with cyclosporine (CsA) after the injection of ethidium bromide (EB) in the rat brainstem 1 . This gliotoxic agent is known to induce early astrocyte disappearance and oligodendroglial loss when injected in the central nervous system (CNS) leading to, respectively, blood-brain barrier disruption and primary demyelination.…”
mentioning
confidence: 99%
“…Several studies reported the invasive capacity of Schwann cells into the CNS from spinal or cranial nerves due to the glia limitans disruption following injection of the gliotoxin [1][2][3][4][5] . This invasion however appeared to be diminished in the diabetic state induced by streptozotocin treatment 6 .…”
Section: Discussionmentioning
confidence: 90%
“…Schwann cell disturbance followed by segmental demyelination in the PNS is a prominent finding in diabetes mellitus of humans 9 and cats 10 , but this is not so commonly observed in spontaneous or experimental diabetes in rats 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations